Business Law - Abbott, Keith, 1952-; Pendlebury, N.; Wardman, Kevin (London : Thomson, 2007)
This textbook is a proven introduction for students on a range of courses who need to get to grips with law for the first time. The author tackles this daunting subject in a no-nonsense way, with a particular emphasis on preparing for exams. It covers the syllabus requirements of the Association of Accounting Technicians (AAT), the Institute of Legal Executives (ILEX) and the Institute of Credit Management (ICM). It is also suitable for the GNVQ Business Law option, undergraduate business and business-related courses such as accounting, and professional courses such as those offered by the ACCA, CIMA, and ICSA.
37. Regulatory Bodies -- Coursework Questions 30-35 -- PART V: COMPANY LAW AND PARTNERSHIPS -- 38. Non Corporate Bodies -- 39. Corporate Bodies- The Company -- 40. The Memorandum and Articles of Association -- 41. Share Capital -- 42. Loan Capital -- 43. Membership and Minority Protection -- 44. Directors and the Secretary -- 45. Auditors and Investigations -- 46. Meetings, Resolutions and Publicity -- 47. Reconstructions, Mergers and Takeovers -- 48. Liquidation, Administration and Receivership -- Coursework Questions 36-42. -- PART VI: EMPLOYMENT LAW -- 49. Employees and Independent Contractors -- 50. The Contract of Employment -- 51. The Common Law Duties of an Employee -- 52. Duties of an Employer -- 53. Wages -- 54. Maternity Rights -- 55. Discrimination -- 56. Termination of Contracts of Employment -- 57. Redundancy -- 58. Social Security -- 59. Industrial Injuries: Employer''s Liability -- 60. Health and Safety at Work -- 61. Institutions and Tribunals -- 62. Trade Unions -- Coursework Questions 43-46 -- Appendices -- Appendix 1: Suggested Answers to Coursework Questions -- Appendix 2: Variants in the Scottish Legal System -- Index.
Includes index.
1
Keywords: Business Law; Business law -- England; Business law -- Wales